Potentiation of High Voltage–Activated Calcium Channels by 4-Aminopyridine Depends on Subunit Composition - Li, Li (Mol Pharmacol, 2014)
4-Aminopyridine (4-AP, fampridine) is used clinically to improve neuromuscular function in patients with multiple sclerosis, spinal cord injury, and myasthenia gravis. 4-AP can increase neuromuscular and synaptic transmission by directly stimulating high voltage–activated (HVA) Ca(2+) channels independent of its blocking effect on voltage-activated K(+) channels. Here we provide new evidence that the potentiating effect of 4-AP on HVA Ca(2+) channels depends on the specific combination of voltage-activated calcium channel α1 (Cavα(1)) and voltage-activated calcium channel β (Cavβ) subunits. Among the four Cavβ subunits examined, Cavβ3 was the most significant subunit involved in the 4-AP–induced potentiation of both L-type and N-type currents. Of particular note, 4-AP at micromolar concentrations selectively potentiated L-type currents reconstituted with Cav1.2, α(2)δ1, and Cavβ3. In contrast, 4-AP potentiated N-type currents only at much higher concentrations and had little effect on P/Q-type currents. In a phrenic nerve–diaphragm preparation, blocking L-type Ca(2+) channels eliminated the potentiating effect of low concentrations of 4-AP on end-plate potentials. Furthermore, 4-AP enhanced the physical interaction of Cav1.2 and Cav2.2 subunits to Cavβ3 and also increased their trafficking to the plasma membrane. Site-directed mutagenesis identified specific regions in the guanylate kinase, HOOK, and C-terminus domains of the Cavβ3 subunit crucial to the ability of 4-AP to potentiate L-type and N-type currents. Our findings indicate that 4-AP potentiates HVA Ca(2+) channels by enhancing reciprocal Cav1.2-Cavβ3 and Cav2.2-Cavβ3 interactions. The therapeutic effect of 4-AP on neuromuscular function is probably mediated by its actions on Cavβ3-containing L-type Ca(2+) channels.